Pergi Belajar Lyric by Mrs. Sud As Transformation Media for Akhlak Education Values - Pangesti, Nofiya Dwi (International Conference of Moslem Society, 2016)
To make human morality necessary educational concept which is not simply to make students know, but how education can make students can applys in his life, it’s called as akhlak education, base to God education, human beings and the environment. Values ​​in the lyrics, especially akhlak education are often used to talk about, but unfortunately, not much to put it in the book. A song lyric is one of values transformation media, that can be transformed to other people that song lyrics to be understood its meaning first. Paul Riceour’s hermeneutic is one of the analysis methode to understand the meaning of a literary work through the analysis of metaphors and symbols, so that the literary work can transforming value to others. Accordingly, this article will discuss about the akhlak education values in pergi belajar lyric by Mrs. Sud using Paul Riceour’s hermeneutic.